2016
DOI: 10.1371/journal.pone.0166198
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Selective Inhibitor of Delta-5 Desaturase Lowers Insulin Resistance and Reduces Body Weight in Diet-Induced Obese C57BL/6J Mice

Abstract: Obesity is now recognized as a state of chronic low-grade inflammation and is called as metabolic inflammation. Delta-5 desaturase (D5D) is an enzyme that metabolizes dihomo-γ-linolenic acid (DGLA) to arachidonic acid (AA). Thus, D5D inhibition increases DGLA (precursor to anti-inflammatory eicosanoids) while decreasing AA (precursor to pro-inflammatory eicosanoids), and could result in synergistic improvement in the low-grade inflammatory state. Here, we demonstrate reduced insulin resistance and the anti-obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…5). As we previously reported (Yashiro et al, 2016), compound-326-treated mice were dose-dependently leaner than the vehicle-treated mice (Fig. 6).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…5). As we previously reported (Yashiro et al, 2016), compound-326-treated mice were dose-dependently leaner than the vehicle-treated mice (Fig. 6).…”
Section: Resultssupporting
confidence: 82%
“…We previously reported that compound-326 (Suzuki et al, 2010), a newly discovered orally available, potent, and selective D5D inhibitor, ameliorated insulin resistance and obesity in a high fat diet-induced obese mouse model accompanied by alterations in the balance between DGLA and AA in the blood (Yashiro et al, 2016). In the present study, we evaluated the antiatherosclerotic effects of compound-326 in Western-diet fed ApoE KO mice.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…AA is a crucial cell membrane component of cells involved in modulating the magnitude and period of inflammatory responses. It exhibits its functions via the synthesis of mostly pro-inflammatory eicosanoids (Calder, 2010 ; Markworth and Cameron-Smith, 2012 ; Yashiro et al, 2016 ). Our phospholipid fraction data show, that the amount of DHGL is negatively influenced by injury in obese mice, while normal weight animals do not show a significant impact, despite higher content.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same SNP in the European population was associated with the lower fasting plasma glucose level in a normal physiological range, but not with pathological glucose levels [179]. Data from multiple experiments on mice suggest that the development of selective desaturases inhibitors can be beneficial in the treatment of human diabetes, obesity, and atherosclerotic cardiovascular disease [180][181][182]. Mice with D6D knockdown developed resistance against high-fat diet induced obesity, so maybe some metabolic benefits for obese people can be gained with D6D inhibitors [183].…”
Section: Role Of Unsaturated Fatty Acid Desaturases In Humans and Othmentioning
confidence: 99%